Menelisik Hoaks Dalam Pemberitaan Konflik Kashmir Di Portal Berita Tahun 2019-2020 - Turpyn, Juan Malik Frederick; Nasucha, Muchammad (CommLine, 2022)
In this era of disruption or digital, various information can be accessed and read widely by anyone connected to the internet, encompassing conflict news in a Country in any part of the world. Unfortunately hoax or fake news is also rampant in cyberspace (online) including appearing in news portals. The assessment of a news story containing hoax information can be seen from several principles of assessment, most fundamentally the inaccuracy in preaching an issue (5W+H: Journalism pattern) in this context is the Kashmir conflict. This has the potential to disrupt mutual harmony, between citizens and between countries because it is charged with humanitarian values or sensitive matters such as religion and belief. The clearest implication is that hoax or fake news can create polarization among the public. Often it seems that some people believe that the hoax is true or does not contain lies, this is what is called as post-truth era. Based on this research the article was created with the aim of finding out if the news hoax kashmir conflict also appeared in the news portal. If so, how and why does the news appear on the news portal. Subsequently, this research article using qualitative research approaches and methods, collecting data online document studies that are news on news portals. The selected case is an identified report containing lies about the Kashmir conflict in the period 2019 – 2020. In sum, based on the data of this study concluded that news portals also do not escape the news hoax, with a variety of news. This happens allegedly to harness the momentum of the conflict in an attempt to attract readers. This is believed to have the potential to greatly polarize public opinion about the Kashmir conflict.